BIOABSORBABLE OSTEOFIXATION MATERIALS IN MAXILLOFACIAL SURGERY: PROGRESS AND FUTURE DIRECTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Rigid fixation is a cornerstone of maxillofacial surgery. Titanium plates and screws have been the gold standard for decades, but complications such as growth restriction in children, radiological artifacts, and the need for secondary removal surgeries have led to the development of bioabsorbable fixation devices. This review summarizes advances in polymer-based and magnesium-based osteofixation systems, their clinical applications, limitations, and future perspectives.